2017
DOI: 10.1620/tjem.241.255
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatitis B Virus Infection in Hyperlipidemia Patients

Abstract: Chronic hepatitis B virus (HBV) infection is associated with lower prevalence of hyperlipidemia (HLP).However, occult HBV infection (OBI) in HLP patients has not yet been explored. OBI is defined as the presence of detectable HBV DNA in serum or liver tissue but undetectable HBV surface antigen in serum. In this study, 1,036 HLP patients and 1,134 replacement blood donor controls were recruited. Among them, 252 HLP patients and 255 blood donors with antibody to HBV core positive were selected and analyzed. HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…As an illustration, OBI prevalence among hemodialysis patients was 1.5% (Turkey), 24 0.5% (Iran), 25 0% (Germany), 26 1.3% (Japan), 27 and 0% (Italy) 28 ; in hemophilia patients was 1.73% in Pakistan, 29 9.3% in Iran, 30 and 0% in Polish 31 ; among thalassemia patients was 31.4% (India), 6 32.5% (Egypt), 5 and 0% (Iran) 13,14 ; in individuals with HCC was 30% (Japan), 32 38.5% (Korea), 33 50% (Egypt), 34 and 70.4% (China) 35 ; among blood donors in different parts of the world was 3.7% (Egypt), 36 4.71% (India), 37 1.98% (Colombia), 38 0.3% (Lebanon), 39 0% (Iran), 8 and 7.4% (Libya). 40 OBI also has been found in patients with leprosy in Brazil (5.3%), 41 individuals suffering from hyperlipidemia in China (9.5%), 42 patients with primary glomerulopathy (3%) and lupus nephritis (13.3%) in Iran, 43 and among ART (antiretroviral therapy) naïve HIV-seropositive individuals in Mozambique (8.3%). 44 Despite other studies in which the frequency of OBI among Iranian BTM patients was0%, 13,14 data obtained in this study showed that one of 86 BTM patients, who were negative for HBsAg, had OBI (1.16%).…”
Section: Resultsmentioning
confidence: 98%
“…As an illustration, OBI prevalence among hemodialysis patients was 1.5% (Turkey), 24 0.5% (Iran), 25 0% (Germany), 26 1.3% (Japan), 27 and 0% (Italy) 28 ; in hemophilia patients was 1.73% in Pakistan, 29 9.3% in Iran, 30 and 0% in Polish 31 ; among thalassemia patients was 31.4% (India), 6 32.5% (Egypt), 5 and 0% (Iran) 13,14 ; in individuals with HCC was 30% (Japan), 32 38.5% (Korea), 33 50% (Egypt), 34 and 70.4% (China) 35 ; among blood donors in different parts of the world was 3.7% (Egypt), 36 4.71% (India), 37 1.98% (Colombia), 38 0.3% (Lebanon), 39 0% (Iran), 8 and 7.4% (Libya). 40 OBI also has been found in patients with leprosy in Brazil (5.3%), 41 individuals suffering from hyperlipidemia in China (9.5%), 42 patients with primary glomerulopathy (3%) and lupus nephritis (13.3%) in Iran, 43 and among ART (antiretroviral therapy) naïve HIV-seropositive individuals in Mozambique (8.3%). 44 Despite other studies in which the frequency of OBI among Iranian BTM patients was0%, 13,14 data obtained in this study showed that one of 86 BTM patients, who were negative for HBsAg, had OBI (1.16%).…”
Section: Resultsmentioning
confidence: 98%
“…According to a cohort study of 1927 patients from 2005 to 2015, hyperlipidemia was correlated with hepatitis progression into hepatocarcinoma without cirrhosis[ 27 ]. Meanwhile, a new type of HBV infection, occult HBV (HBV DNA-positive, but HBV surface antigen-negative), is more likely to occur in patients with hyperlipidemia[ 28 ]. The molecular mechanisms by which hyperlipidemia interacts with hepatitis remain unknown; however, an interesting phenomenon between hyperlipidemia and HBV infection has been reported.…”
Section: Discussionmentioning
confidence: 99%